Vitex trifolia’s molecular anti-inflammatory effect: a review - Tamim Ghafari, Ahmad; Hasyila Jahidin, Aisyah; Zakaria, Yuslina; Hazizul Hasan, Mizaton (Science, Engineering and Health Studies, 2021)
Inflammation is defined as a defensive response of the body against invading agents and harmful stimuli directly involved in the pathophysiology of various chronic diseases. Conventional anti-inflammatories have always been the first choice to treat and control inflammation and inflammation-related diseases. However, researchers have been searching for safer alternatives to conventional drugs with fewer possible side effects. Medicinal plants are considered potent alternatives to these drugs. Thus, understanding the molecular mechanisms of these plants and their biological targets can provide a new prospect for developing new anti-inflammatory agents with safer effects. Vitex trifolia belongs to the family Verbenaceae, a multipurpose medicinal plant, which can exhibit anti-inflammatory property. In recent literature, the plant was reported to have significant anti-inflammatory actions, including inhibitory effects on pro-inflammatory signaling pathways and mediators. Herein, the molecular anti-inflammatory effects of Vitex trifolia and its active components during inflammation have been reviewed.